2017
DOI: 10.1037/hea0000505
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioral therapy for body image and self-care (CBT-BISC) in sexual minority men living with HIV: A randomized controlled trial.

Abstract: Objective Body image disturbance is a distressing and interfering problem among many sexual minority men living with HIV, and is associated with elevated depressive symptoms and poor HIV self-care (e.g., antiretroviral therapy [ART] non-adherence). The current study tested the preliminary efficacy of a newly created intervention: cognitive behavioral therapy for body image and self-care (CBT-BISC) for this population. Methods The current study entailed a two-arm randomized controlled trial (N = 44) comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 66 publications
1
52
0
2
Order By: Relevance
“…Results from a previous study [22] demonstrated preliminary efficacy of CBT-BISC, but did not examine the mechanisms by which the intervention improved ART adherence. We found that participants in the CBT-BISC condition displayed substantial reductions in body image disturbance and depression, as well as improved global functioning, at the end of the intervention and at follow-up as compared to the treatment as usual group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Results from a previous study [22] demonstrated preliminary efficacy of CBT-BISC, but did not examine the mechanisms by which the intervention improved ART adherence. We found that participants in the CBT-BISC condition displayed substantial reductions in body image disturbance and depression, as well as improved global functioning, at the end of the intervention and at follow-up as compared to the treatment as usual group.…”
Section: Discussionmentioning
confidence: 99%
“…Treating body image disturbance may also increase ART adherence, thereby reducing viral load, and ultimately reducing the risk of transmission of HIV [20] which is important to both individual patients and public health. Clinicians may want to consider utilizing the CBT-BISC modules found in the primary outcome paper [22] during treatment, as it has been shown to effectively improve ART adherence and reduce body image concerns. In sum, these findings have implications for clinical practice, as screening for and targeting body image disturbance may be an important step in improving ART adherence and reducing HIV transmission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations